Normative Data of the Interorbital Distance in Thai Population. Issue 7 (October 2018) - Chatdokmaiprai, Chalermpong; Kiranantawat, Kidakorn; Lertsithichai, Panuwat; Taeshineetanakul, Patamintita
Abstract : Abstract: The incidence of the patients with craniofacial anomalies was high in southeast-Asian countries, for example, fronto-ethmoidal encephalo-menigocele or craniosynostosis. These craniofacial anomalies usually involve orbits, so a surgical orbital reconstruction is always required. Various methods have been used in the past to indirectly analyze the craniofacial region. Plain skull radiography, anthropometry, and cephalometry provided the limited information of interorbital distance in terms of accuracy whereas the interorbital distance is crucial to be reconstructed, increasing or decreasing. The accurate normal interorbital distance which grows by age as other craniofacial structures is the important data in the part of interorbital and orbital reconstruction. To date, the normative data of the bony interorbital distance among Thai population have not been established. The purpose of this study is to provide normal values and the growth patterns of the bony interorbital distances and other dimensions of the orbit according to age among Thai population through the axial computed tomography. Comparisons can then be made between normal values and those for an individual patient or those for a group of patients, for example, those with front-ethmoidal meningoencephalocele, Crouzon, or Treacher–Collins syndrome, or among values for individual patients at different time intervals. A retrospective study of computed tomography (CT) scan series of 698 normal orbits from 349 skeletally normal subjects (202 men and 147 women) was enrolled. The age range of the patients was 0 to 21 years (mean, 10.2 years; SD, 5.8 years). A series of 12 measurements were obtained from the CT scans of each subject. All CT images were obtained from patients who underwent CT of the facial bone, brain, and orbits at the Department of Radiology of 3 big hospital in Bangkok–Ramathibodi, Samitivej Srinakarin, and Bangkok hospital–since 2010 to 2015. The normal measurement values in the orbital region through the CT images, as the normal periorbital growth curve, will help improving diagnostic accuracy, staging of reconstruction, precision of corrective surgery, and follow-up of the Thai patients with craniofacial abnormalities such as front-ethmoidal meningoencephalocele, hypertelorism. These data may also apply to the related population in the southeast-Asian countries.